Tolerance, immunosuppression, and immune modulation: impacts on lung allograft survival. Issue 3 (June 2021) - Shepherd, Hailey M.; Gauthier, Jason M.; Kreisel, Daniel
Abstract : Purpose of review: Immune responses following lung transplantation continue to result in high rates of allograft failure and rejection, and current immunosuppression does not address the unique immunologic properties of the lung. Here, we review recent studies on lung allograft tolerance and alloimmunity and discuss implications for immunosuppression. Recent findings: Processes governing tolerance and alloimmunity in lung allografts differ from other solid organs. Recent studies have suggested that allorecognition is regulated at the level of the lung graft. Furthermore, certain cell populations essential for lung allograft tolerance may facilitate rejection in other organs. Induction of lung allograft tolerance is associated with the formation of tertiary lymphoid organs, which are enriched in regulatory T cells and play an important role in preventing rejection. Summary: Recent discoveries regarding alloactivation and the regulation of tolerance following lung transplantation have introduced exciting potential avenues for the development of lung-specific immunosuppression.